RESEARCH OF VOLTAMPER CHARACTERISTICS OF SEMICONDUCTOR STRUCTURES AND DEVICES - E.A. Pecherskaya; O.V. Karpanin; D.E. Nelyutskovа; M.A. Nelyutskov; V.S. Aleksandrov; A.E. Zhurina (Измерение, мониторинг, управление, контроль, 2024)
Background. The object of study is an automated measuring system designed to measure the electrical parameters of semiconductor structures and devices. The subject of the study is the current-voltage characteristics of semiconductor structures and devices. The purpose of the work is to study the current-voltage characteristics of semiconductors using the example of a KT306A silicon transistor using an automated measuring system. Materials and methods. The structure of an automated measuring system for studying the current-voltage characteristics of semiconductor structures and devices is considered. The operating principles of the following methods for measuring semiconductor characteristics have been tested: voltmeter-ammeter, capacitive divider, bridge and resonant. Results. The volt-ampere characteristic of the KT306A silicon transistor was studied using an automated measuring system. The possibility of using the proposed measuring instrument to study the volt–ampere characteristics of TIR structures (metal-dielectric-semiconductor) when using a layer of tin dioxide doped with antimony as a transparent conductive oxide is shown. Conclusions. The structure of an automated measuring system for studying the volt-ampere characteristics of semiconductors is considered. The results of the approbation of this system are presented when measuring the electrophysical parameters of the KT306A semiconductor transistor, as well as the new metal-dielectric-semiconductor structure obtained by the authors based on antimony- doped tin dioxide synthesized by spray pyrolysis.